The Impact of Operational Efficiency and Asset Structure on the Cash Conversion Cycle: A Case Study of Manufacturing Companies in the Healthcare Subsector Listed on the Indonesia Stock Exchange, 2020–2024 - Riska Amalia Nur Khasanah; Rakhmat Siraz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The significance of working capital management in preserving a business's cash flow, especially in the healthcare sector with its comparatively complicated inventory, accounts receivable, and operational needs, is the driving force behind this study. A causal-associative study with a quantitative technique is the research approach used. The data used for the study comes from company annual reports that were made public by the Indonesia Stock Exchange during the time the study was conducted. The research is based on healthcare manufacturing companies that are listed on the Indonesia Stock Exchange. Ten businesses were chosen as the research sample using predetermined criteria and a purposive sampling technique. Fifty data observations were gathered over the five-year observation period. Data analysis makes use of these techniques. Fifty data observations were gathered over the five-year observation period. Descriptive statistical analysis, multiple linear regression analysis, t-tests, F-tests, classical assumption tests, and the coefficient of determination using IBM SPSS 27 are some of the data analysis techniques employed. The findings show that “while asset structure has no effect on the cash conversion cycle, operational efficiency does.” Concurrently, “the cash conversion cycle is not significantly impacted by either asset structure or operational effectiveness.” Additionally, operational efficiency is the most significant factor influencing the cash conversion cycle.